Children’s Internet Use, Self-Reported Life Satisfaction, and Parental Mediation in Europe: An Analysis of the EU Kids Online Dataset - Milosevic, Tijana; Kuldas, Seffetullah; Sargioti, Aikaterini; Laffan, Derek A.; O’Higgins Norman, James (Frontiers in Psychology, 2022)
The present research examines how children’s time spent online is associated with their perceived life satisfaction accounting for their age, gender, socio-economic status, emotional problems, country, and family environmental factors. This research article is based on the data of the large scale cross-sectional EU Kids Online survey undertaken in 16 European countries with nationally representative samples of children aged 9-17 (N = 11,200, Mage = 13.3, SD = 2.36; 50.6% Boys, 49.4% Girls). The results indicated that the time children spent online appeared to have no considerable negative effect on their self-reported life satisfaction. Comparatively, the positive effects of children’s parental socio-economic status and family environment accounted for 43% of the overall 50% of the variance in children’s self-reported life satisfaction scores. Considering that children’s socio-economic status alone accounted for 42% of the variance, children’s emotional problems, country of residence, and enabling parental mediation accounted for the remaining 3%, 4%, and 1% of the variance respectively. In line with previous studies that urge caution when discussing the negative influence of time spent online on children’s mental health and overall wellbeing, the current findings suggest that social-ecological characteristics and how children use the Internet, need to be examined further.